Morphology‐function relationships and repeatability in the sperm of Passer sparrows. (26th November 2014) - Cramer, Emily R.A.; Laskemoen, Terje; Stensrud, Even; Rowe, Melissah; Haas, Fredrik; Lifjeld, Jan T.; Sætre, Glenn‐Peter; Johnsen, Arild
ABSTRACT Sperm performance is likely to be an important determinant of male reproductive success, especially when females copulate with multiple males. Understanding sperm performance is therefore crucial to fully understand the evolution of male reproductive strategies. In this study, we examined the repeatability of sperm morphology and motility measures over three breeding seasons, and we studied relationships between sperm morphology and function. We conducted this study in wild‐derived captive house sparrows (Passer domesticus) and Spanish sparrows (P. hispaniolensis). Results for the two species were similar. As predicted from results in other passerine species, total sperm length was highly repeatable across ejaculates, and repeatability for the length of other components was moderate. The repeatability of sperm swimming speed across ejaculates was lower, but statistically significant, suggesting that sperm velocity may be a relatively dynamic trait. Surprisingly, swimming speed did not correlate with the relative length of the midpiece, and it correlated negatively with the relative length of the flagellum and with total sperm length. This pattern is the opposite of what theory predicts and differs from what has been found in house sparrows before. Also contrary to previous work, we found no evidence that total sperm length correlates with sperm longevity. These results therefore highlight the need for a better understanding of relationships between sperm morphology and function in passerine birds. J. Morphol. 276:370–377, 2015. © 2014 Wiley Periodicals, Inc.